Avaliação da implementação do ensino remoto emergencial e suas implicações no trabalho docente na educação superior, no contexto da pandemia de covid 19, em Fortaleza-CE - Sales, Josefa Braga Cavalcante (2021)
It comes from a personal restlessness marked by an unimagined experience and the determination to investigate the conditions of teaching work in the 2020 pandemic period in private Higher Education Institutions (IES) in Fortaleza, Ceará. The aim is to understand the perception of teachers who have had the experience of working with emergency remote teaching (ERE) in the period of the covid-19 pandemic, and, more broadly, to evaluate the policy of implementing the ERE in higher education and the its imbrication in the teaching work, since the atypical period. This is an evaluative research of a qualitative, descriptive nature, with analysis of authorization documents issued during the pandemic period. Data collection was carried out through the application of a self-administered online questionnaire, made available by the Google Forms platform, and interviews opened through virtual means. Content analysis from the perspective of Bardin (1977) followed the stages of pre-analysis, material exploration, treatment of results, inference and interpretation. The In-Depth Assessment (RODRIGUES, GUSSI, 2008) was the theoretical-methodological and political proposal chosen to guide the research, with a view to providing work on the policy content, context, and how subjects understand the lived moment based on their experiences. . The results showed that teachers who were active in 2020 were not prepared for remote teaching, nor did they have specific training to work in technology-mediated courses before the pandemic, which produced a self-perception of unpreparedness and feelings such as fear, insecurity and anguish - potentiated by the difficulties faced by teachers due to the lack of interaction and students' interest in remote teaching. The perspective for professionals is that technology-mediated teaching is here to stay and that it makes teaching work even more precarious.